Improving Mathematical Problem-Solving Junior High School Through Contextual Teaching and Learning - Rohimatunisa, Dela; Sudianto, Sudianto (Al-Mufid, 2023)
This study aims to compare the improvement in mathematical problem-solving skills between students using a contextual approach and those using conventional learning. The research focuses on the Initial Mathematical Ability (KAM) category of high-ability students. A quasi-experimental design was employed, with a non-equivalent pre- and post-test control group. The Two-Way Anova test was utilized for data analysis, with a significance value of 0.003. The results showed a significant difference in improving mathematical problem-solving ability between the two groups. The contextual approach proved particularly beneficial for high-ability students. However, it is essential to consider other factors influencing improvement. This study provides insights into effective mathematics instruction, emphasizing the importance of relevant and applicable learning experiences to enhance problem-solving abilities. Further research should explore long-term effects and adaptation for students with varying initial abilities. These findings contribute to developing more effective mathematics curricula and learning strategies, ultimately improving students' problem-solving skills.